2016
DOI: 10.20960/nh.125
|View full text |Cite
|
Sign up to set email alerts
|

La suplementación con antioxidantes durante el tratamiento oncológico no tiene efecto sobre la recurrencia de cáncer cervicouterino

Abstract: Introducción y objetivos: la terapia con antioxidantes durante la quimioterapia y radioterapia en pacientes con cáncer cervicouterino es controvertida. Mientras existe evidencia que sugiere que el uso de antioxidantes disminuye los efectos secundarios propios del tratamiento contra el cáncer, hay datos que sugieren que los antioxidantes incrementan el riesgo de recurrencia de cáncer por la afectación de la terapia de los tratamientos. Métodos: se dirigió un estudio clínico controlado en pacientes con cáncer ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…This is because cancer cells have redox regulation genes, suggesting that low ROS levels are required for their survival; however, the therapeutic approach may be crucial to treating this pathology. Nevertheless, in clinical trials has been shown that antioxidant consumption might be beneficial [ 167 , 168 , 169 , 170 , 171 , 172 ] or have no effect [ 167 , 172 , 173 , 174 ], as it is suggested to depend on the metabolic demand of the individual.…”
Section: Inflammation In Cancermentioning
confidence: 99%
“…This is because cancer cells have redox regulation genes, suggesting that low ROS levels are required for their survival; however, the therapeutic approach may be crucial to treating this pathology. Nevertheless, in clinical trials has been shown that antioxidant consumption might be beneficial [ 167 , 168 , 169 , 170 , 171 , 172 ] or have no effect [ 167 , 172 , 173 , 174 ], as it is suggested to depend on the metabolic demand of the individual.…”
Section: Inflammation In Cancermentioning
confidence: 99%
“…These results are similar to those documented in patients recently admitted to the oncology department of a general hospital in Mexico, where weight loss greater than 5% occurred in 40.3% of cases, stratified as mild loss (8.8%), moderate (9.7%) or severe (21.8%). 13 Nevertheless, Fernández-López et al (2013) 12 documented that 69% of cancer patients in their sample lost more than 5% of their usual weight over the 3 months prior to treatment with the highest frequency among those with tumors of the digestive tract.…”
Section: Discussionmentioning
confidence: 98%
“…The prevalence of compromised nutritional status in our study is consistent with results of studies by other researchers. [10][11][12][13] Based on the NRS-2002, severe nutritional risk was documented in 50% of patients before the start of cancer treatment 13 and in 76% of individuals with various types of cancers. 11 Among patients recently hospitalized with various types of cancer, the use of Patient-Generated Subjective Global Assessment protocol showed varying degrees of malnutrition in about 70% of cases.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations